CPOUP IN CHІLDREN - Пікуль, К.В. (World of Medicine and Biology, 2013)
The article provides a literature review of the syndrome of acute stenosing laryngotracheitis and Easten croup in children. The authors consider the major clinical diagnostic criteria and the provision of emergency assistance to children with this syndrome.